Risk factors for developing diabetic foot - Julia Estela Willrich Boell; Renata Mafra Ribeiro; Denise Maria Guerreiro Vieira da Silva (Universidade Federal de Goias, 2014)
The goal of the present study is to identify the risk factors for developing diabetic foot. A cross-sectional study, with a convenience sample, developed with 70 individuals with diabetes mellitus (DM), registered in three basic health units in the municipality of Florianópolis/SC, Brazil, in the period from November 2010 to May 2011. Biometric data was collected regarding their sociodemographic, health and illness conditions. An assessment of the feet was also carried out. The average participant age was 66.17 years and time with diagnosed disease was under ten years (61.42%). The following risk factors were identified: advanced age; time of DM diagnosis; few years of schooling; overweight/obesity; inadequate diet; physical inactivity; inadequate metabolic control; lack of proper and specific foot care; and arterial hypertension. We conclude that the majority of the population presented one or more risk factors that favor the appearance of foot-related complications. doi: 10.5216/ree.v16i2.20460.